Hypoxia-altered cholesterol homeostasis enhances the expression of interferon-stimulated genes upon SARS-CoV-2 infections in monocytes - Bauer, Rebekka; Meyer, Sofie Patrizia; Raue, Rebecca; Palmer, Megan A.; Guerrero Ruiz, Vanesa Maria; Cardamone, Giulia; Rösser, Silvia; Heffels, Milou; Roesmann, Fabian; Wilhelm, Alexander; Lütjohann, Dieter; Zarnack, Kathi; et al. (Frontiers in Immunology, 2023)
Hypoxia contributes to numerous pathophysiological conditions including inflammation-associated diseases. We characterize the impact of hypoxia on the immunometabolic cross-talk between cholesterol and interferon (IFN) responses. Specifically, hypoxia reduced cholesterol biosynthesis flux and provoked a compensatory activation of sterol regulatory element-binding protein 2 (SREBP2) in monocytes. Concomitantly, a broad range of interferon-stimulated genes (ISGs) increased under hypoxia in the absence of an inflammatory stimulus. While changes in cholesterol biosynthesis intermediates and SREBP2 activity did not contribute to hypoxic ISG induction, intracellular cholesterol distribution appeared critical to enhance hypoxic expression of chemokine ISGs. Importantly, hypoxia further boosted chemokine ISG expression in monocytes upon infection with severe acute respiratory syndrome coronavirus type 2 (SARS-CoV-2). Mechanistically, hypoxia sensitized toll-like receptor 4 (TLR4) signaling to activation by SARS-CoV-2 spike protein, which emerged as a major signaling hub to enhance chemokine ISG induction following SARS-CoV-2 infection of hypoxic monocytes. These data depict a hypoxia-regulated immunometabolic mechanism with implications for the development of systemic inflammatory responses in severe cases of coronavirus disease-2019 (COVID-19).